Pengaruh Manajemen Laba dan Ukuran Perusahaan pada Beban Pajak Tangguhan - Anggara, Hendy; Sukartha, I Made (E-Jurnal Akuntansi, 2018)
Indonesian is one of the countries that rely on tax revenue as the main source of state income. The income tax-oriented accounting method of accounting recognizes deferred tax liabilities and assets against future fiscal consequences caused by temporary differences and residual losses that have not been compensated. The temporary differences that lead to an increase in future tax amount will be recognized as deferred tax liabilities, therefore the company must recognize a deferred tax burden.  The purpose of this study is to obtain empirical evidence of the influence of earnings management and firm size on deferred tax expense. The sample in this study is a company listed on the Indonesia Stock Exchange in 2012-2016 amounting to 10 companies using purposive sampling method. Deferred tax expense can be measured by the total deferred tax expense per year divided by the total assets of the company per year. The results showed that earnings management had a negative effect on deferred tax expense, and firm size had a positive effect on deferred tax expense